2018
DOI: 10.1016/j.ijsu.2018.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hook plate with versus without double-tunnel coracoclavicular ligament reconstruction for repair of acute acromioclavicular joint dislocations: A prospective randomized controlled clinical trial

Abstract: The overall surgical effect of the use of a hook plate combined with double-tunnel CC ligament reconstruction is superior to single hook plate surgery for the repair of acute Rockwood type III and V AC joint dislocations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…Yin et al reported a similar outcome following study of the use of a hook plate with or without double-tunnel coracoclavicular ligament reconstruction. In the hook plate xation alone group, six patients had loss of reduction (23.08%), and 12 patients had acromion cortex erosion, but no related complications were observed in the ligament reconstruction group [21]. In this study, we observed a similar CMS in the HM and HP groups (94.0±6.54 versus 94.2±7.35, p= 0.75); however, the grade of loss of reduction was better in the HM group 12 months after surgery (100.75±48.70 versus 91.47±27.47, p= 0.015), indicating that the HM group exhibited superior reduction maintenance over the HP group.…”
Section: Discussionmentioning
confidence: 92%
“…Yin et al reported a similar outcome following study of the use of a hook plate with or without double-tunnel coracoclavicular ligament reconstruction. In the hook plate xation alone group, six patients had loss of reduction (23.08%), and 12 patients had acromion cortex erosion, but no related complications were observed in the ligament reconstruction group [21]. In this study, we observed a similar CMS in the HM and HP groups (94.0±6.54 versus 94.2±7.35, p= 0.75); however, the grade of loss of reduction was better in the HM group 12 months after surgery (100.75±48.70 versus 91.47±27.47, p= 0.015), indicating that the HM group exhibited superior reduction maintenance over the HP group.…”
Section: Discussionmentioning
confidence: 92%
“…Yin et al reported a similar outcome following study of the use of a hook plate with or without double-tunnel coracoclavicular ligament reconstruction. In the hook plate xation alone group, six patients had loss of reduction (23.08%), and 12 patients had acromion cortex erosion, but no related complications were observed in the ligament reconstruction group [21]. In this study, we observed a similar CMS in the HM and HP groups (94.0±6.54 versus 94.2±7.35, p= 0.75); however, the grade of loss of reduction was better in the HM group 12 months after surgery (100.75±48.70 versus 91.47±27.47, p= 0.015), indicating that the HM group exhibited the statistical differences in reduction maintenance over the HP group.…”
Section: Discussionmentioning
confidence: 92%
“…However, hook plates may be combined with ligament reconstruction. For example, Yin et al concluded that hook plating combined with a double-tunnel CC reconstruction showed superior results to hook plating alone [20]. Although hook plate osteosynthesis is a simple procedure, a second procedure for hardware removal is required.…”
Section: Discussionmentioning
confidence: 99%